Comprehensive geriatric assessment, frailty and sarcopenia in elderly surgical patients: a narrative review of evidence - King Fan Yip; Sachin Mathur; Chuen Chai Dennis Seow (Proceedings of Singapore Healthcare)
Background: As the number of elderly undergoing surgical procedures increases with our aging population, the risk of adverse surgical outcomes also increases with reduced physiological reserve, multiple comorbidities, frailty and functional disability. Objectives: As Comprehensive Geriatric Assessment (CGA) is increasingly being integrated as part of good surgical care for older patients owing to better patient outcomes, this review aims to provide an overview of the current evidence regarding its benefit on geriatric surgical patients among different surgical specialties, with additional focus on patients with frailty and/ or sarcopenia. Methods: Using chosen keywords, searches were conducted using Pubmed, Google scholar and Cochrane Library. Inclusion criteria were surgery of various specialties with the exception of orthopaedic surgery, and studies published in English only. Exclusion criteria were orthopaedic surgery, and non-English articles. Prospective, retrospective, randomized controlled and cohort studies were considered given the limited number of studies published thus far. Relevant journal articles referenced in the chosen articles were also referenced in writing this narrative review. Only the most relevant articles from 2010 onwards were used as earlier ones were outdated. Results & Conclusion: There is evidence of good outcomes after performing CGA and screening for frailty and sarcopenia in elective surgical patients while evidence on the usage of CGA for emergency surgical patients perioperatively is limited. Future studies could focus on the challenges to integrating CGA (including screening for frailty and sarcopenia) as part of routine surgical care and healthcare outcomes.